2021
DOI: 10.1002/asia.202100244
|View full text |Cite
|
Sign up to set email alerts
|

Palladium/Zinc Co‐Catalyzed Asymmetric Hydrogenation of γ‐Keto Carboxylic Acids

Abstract: A palladium‐catalyzed asymmetric hydrogenation of levulinic acid has been successful developed by using Zn(OTf)2 as co‐catalyst. The present method not only has provided a strategy in the palladium‐catalyzed asymmetric hydrogenation of ketone, but also allowed the preparation of a wide range of chiral γ‐valerolactones in good yields with excellent enantioselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…[8][9][10] g-Lactones are important biologically active molecules and provide building blocks for various fine chemicals (Scheme 1a). [11][12][13][14][15][16] Scheme 1. a) Importance of g-lactones as flavor and fragrance and biologically active compounds. [17][18][19] b) Literature-reported enzymatic conversion of 1,4-keto esters/acids into g-lactones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] g-Lactones are important biologically active molecules and provide building blocks for various fine chemicals (Scheme 1a). [11][12][13][14][15][16] Scheme 1. a) Importance of g-lactones as flavor and fragrance and biologically active compounds. [17][18][19] b) Literature-reported enzymatic conversion of 1,4-keto esters/acids into g-lactones.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] γ-Lactones are important biologically active molecules and provide building blocks for various fine chemicals (Scheme 1a). [11][12][13][14][15][16] Moreover, they are highly relevant structures both in the food and cosmetic industries as flavors and fragrances. [24] For instance, γ-decalactone provides a characteristic aroma of peaches.…”
Section: Introductionmentioning
confidence: 99%
“…Transition-metal-catalyzed asymmetric hydrogenation of ketones has been among the most important chiral alcohol formation methods in modern organic synthesis thus far because of its high efficiency, environmental friendliness, and low cost . Most reported chiral catalysts derived from noble-metal precursors (mainly Ru, Ir, and Pd) exhibit high activity and enantioselectivity. , For example, Noyori, Ohkuma, and Zhang , carried out Ru­(II)-catalyzed asymmetric hydrogenation of γ-keto acids or esters with high enantioselectivity. Zhou et al developed a protocol for providing chiral γ-lactones in excellent enantioselectivity using chiral spiro iridium catalysts. , Recently, Fan’s group reported palladium/zinc co-catalyzed asymmetric hydrogenation of γ-ketocarboxylic acids for the synthesis of chiral lactones…”
mentioning
confidence: 99%
“…13 In 2021, a palladium-catalyzed asymmetric hydrogenation of g-keto carboxylic acids was successfully developed by using Zn(OTf) 2 as a co-catalyst by Fan and coworkers, which produced chiral g-lactones with high yields and enantioselectivities (Scheme 2(d)). 14 Although various strategies for the synthesis of chiral lactones have been developed, these methods always involve high catalyst loading, critical temperature, and time-consuming and environmentally unfriendly processes. Furthermore, few previous studies involving the asymmetric hydrogenation of biarylbridged ketoesters have been reported, the products of which are biaryl-bridged seven-membered lactones.…”
mentioning
confidence: 99%
“…13 In 2021, a palladium-catalyzed asymmetric hydrogenation of γ-keto carboxylic acids was successfully developed by using Zn(OTf) 2 as a co-catalyst by Fan and coworkers, which produced chiral γ-lactones with high yields and enantioselectivities (Scheme 2(d)). 14…”
mentioning
confidence: 99%